P-CORDIC: A Precomputation Based Rotation CORDIC Algorithm - Parhi Keshab K (EURASIP Journal on Advances in Signal Processing, 2002)
This paper presents a CORDIC (coordinate rotation digital computer) algorithm and architecture for the rotation mode in which the directions of all micro-rotations are precomputed while maintaining a constant scale factor. Thus, an examination of the sign of the angle after each iteration is no longer required. The algorithm is capable to perform the CORDIC computation for an operand word-length of 54 bits. Additionally, there is a higher degree of freedom in choosing the pipeline cutsets due to the novel feature of independence of the iterations and in the CORDIC rotation.